Relevansi Materi PAI Dengan Tuntutan Kemajuan Ilmu Pengetahuan Dan Teknologi: Sebuah Tinjauan Literatur - Subiantoro, Subiantoro (Jurnal Pendidikan Tambusai, 2024)
The rapid development of science and technology in recent years requires an adjustment of Islamic Religious Education (PAI) materials to remain relevant and contextual. Some previous studies indicate that there is currently a gap between Islamic Education materials and the demands of the times. This study aims to conduct a systematic literature review of the relevance of Islamic Education materials in the context of scientific and technological advances. The research method used was a literature review by analyzing scientific articles related to the research topic from various journal databases. The results of the literature review showed that: (1) the development of science and technology and digital information affects PAI methods and materials; (2) the need to revise PAI materials to be relevant to universal religious values; (3) emphasis on critical thinking skills and digital literacy; (4) PAI materials have not optimally developed the affective and psychomotor aspects of students; and (5) transformation of PAI teaching materials and methods is needed. The study recommends the integration of digital content, contextual and humanist approaches, and increased teacher competence to maintain the relevance of PAI. Further research related to the implementation of these recommendations is also suggested